2008
DOI: 10.3855/jidc.268
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal brucellosis on pregnancy outcome

Abstract: Background: Our aim was to assess the outcome of pregnancies complicated by Brucella infection. Design: Prospective study. Setting: EL-Hasan National Hospital, El-Rawad Clinic, TAIF, SAUDI ARABIA (where the practical part of the study was accomplished) and Obstetrics & Gynecology Department, Mansoura University Hospital (where the theoretical part of the study was completed). Methods: This study was conducted from August 2005 to December 2007. Tube method for detection of antibody titre for brucellosis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 22 publications
6
78
3
3
Order By: Relevance
“…This association is disputed in peer-reviewed literature [47,48]. However, multiple studies hold that there is a true association between brucellosis infection and spontaneous abortions and fetal deaths [47,49–52]. This association could be explained by maternal toxemia, disseminated intravascular coagulation, or simply bacteremia.…”
Section: Pathogenesis Clinical Presentation and Risk Factor In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…This association is disputed in peer-reviewed literature [47,48]. However, multiple studies hold that there is a true association between brucellosis infection and spontaneous abortions and fetal deaths [47,49–52]. This association could be explained by maternal toxemia, disseminated intravascular coagulation, or simply bacteremia.…”
Section: Pathogenesis Clinical Presentation and Risk Factor In Humansmentioning
confidence: 99%
“…Spontaneous abortion and fetal death was statistically associated with seropositivity. However, there was no increased risk for preterm labor in brucellosis-infected mothers [49,51]. …”
Section: Pathogenesis Clinical Presentation and Risk Factor In Humansmentioning
confidence: 99%
“…It is well established that a number of zoonotic pathogens, including Toxoplasma gondii, Listeria monocytogenes, certain Chlamydia species, and Coxiella burnetii, may constitute a risk for the pregnant woman and her fetus [1][2][3][4][5][6][7]. By contrast, pregnancy outcome following other zoonotic infections including Salmonella, Campylobacter, Yersinia enterocolitica and Brucella is more sparsely described [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Brucella seropositivity is not more common in women with spontaneous abortion or miscarriage than in women with uncomplicated pregnancies [141,142]. Some studies have shown that there is no correlation between the magnitude of Brucella agglutination titer and the occurrence of spontaneous abortion while others have shown that Brucella titers higher than 1:160 are associated with higher probability of spontaneous abortion [38, 130,136,143].…”
Section: Brucellosis In Pregnancymentioning
confidence: 99%
“…Occasionally, it may be complicated by Brucella bacteremia, septic shock, neurobrucellosis and disseminated intravascular coagulation (DIC) [131,132]. Brucellosis in pregnancy may predispose to spontaneous abortion, intrauterine fetal death, premature delivery, low birth weight in addition to postpartum intrauterine infections [1,130,[133][134][135][136][137][138][139]. Vaginal bleeding at presentation may be an early sign of spontaneous abortion.…”
Section: Brucellosis In Pregnancymentioning
confidence: 99%